2010
DOI: 10.18321/ectj30
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Nanocrystalline Hydroxyapatite Coating

Abstract: A novel approach for depositing of hydroxyapatite (HA) films on titanium substrates by using high energy ball milling (HEBM) has been developed. It was demonstrated that a heat treatment of the mechanically coated HA at 800 °C for one hour leads to partial transformation of HA phase to -TCP. It appears that the grain boundary and interface defects formed during MCS reduce this characteristic transformation temperature. Also, it was shown that Ti incorporation into the HA structure causes the lattice shrinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
4
4
0
Order By: Relevance
“…Similar results were obtained in another study [666]. According to the authors, the impacts of the milling balls both significantly decreased the dimensions of the HA particles and simultaneously activated the metal surface, which led to the robust cold-welding of HA particles to the metal surface [665,666]. No information on the properties of deposits was disclosed.…”
Section: Mechanochemical Synthesis or Ball Impact Techniquesupporting
confidence: 57%
See 2 more Smart Citations
“…Similar results were obtained in another study [666]. According to the authors, the impacts of the milling balls both significantly decreased the dimensions of the HA particles and simultaneously activated the metal surface, which led to the robust cold-welding of HA particles to the metal surface [665,666]. No information on the properties of deposits was disclosed.…”
Section: Mechanochemical Synthesis or Ball Impact Techniquesupporting
confidence: 57%
“…To prevent contamination from the atmosphere, the chamber was sealed. Deposits of ~ 50 μm thick were put down as the result [665]. Similar results were obtained in another study [666].…”
Section: Mechanochemical Synthesis or Ball Impact Techniquesupporting
confidence: 56%
See 1 more Smart Citation
“…Large amounts of plastic deformation result in the generation of a variety of defect structures (dislocations, vacancies, stacking faults, grain boundaries, etc.) and these destabilize the ordered nature of the lattice leading to the formation of a disordered (crystalline or amorphous) phase [8,9]. The amorphization process starts when the substrate has experienced a certain number of critical collisions which depend on the impact energy.…”
Section: Resultsmentioning
confidence: 99%
“…SMAT involves repeated multidirectional impact by flying balls to induce surface hardening of bulk samples. The impact causes severe plastic deformation in the surface layer of the treated sample, leading to grain refinement, large grain boundary misorientation, dislocation blocks and microbands [5][6][7][8]. Recent investigations have demonstrated that commercially pure titanium with an ultrafine grain structure in the nanometer range can be processed using severe plastic deformation methods such as equal channel angular pressing and high pressure torsion [3,8].…”
Section: Introductionmentioning
confidence: 99%